The Mapping of Quality Tourists Prospects for Indonesia’s Tourism Markets - Maulana, Addin; Koesfardani, RR Chamma Fitri Putri Pradjwalita; Richard Alan Amory, I Dewa Gede (Binus Business Review, 2020)
The research aimed to identify which countries could be segmented as a potential tourism market for Indonesia to increase quality tourists. It applied quantitative methods with descriptive statistical analysis techniques to describe the average expenditure per visit and the length of stay. It was conducted by modifying the quadrant model. The result shows that there are countries included in the market with the prospect of quality tourists. Those are Saudi Arabia, Netherlands, Sweden, Switzerland, Belgium, Russia, France, Germany, Austria, Finland, Italy, Spain, Norway, Denmark, Canada, United Kingdom, New Zealand, USA, Portugal, Egypt, Pakistan, and Australia. The government needs to optimize those countries to become the main market. Therefore, the revenue from the tourism sector can be better optimized.